Spread of Antifungal-Resistant Trichophyton indotineae, United Kingdom, 2017–2024 - Alireza Abdolrasouli; Richard C. Barton; Andrew M. Borman (Emerging Infectious Diseases)
We describe 157 cases of Trichophyton indotineae infection in the United Kingdom, mostly in patients linked to southern Asia. T. indotineae is spreading in the United Kingdom and accounts for 38% of dermatophyte isolates referred to the UK National Mycology Reference Laboratory. Clinicians should suspect T. indotineae in tinea corporis cases.